Design of a CMOS class AB amplifier - Sun, Shenghao (2014)
Power amplifier is one of the most important and used structure in the VLSI design. Due to the development of operational transconductance amplifiers (OTA), which are only able to drive capacitance load, thus an output stage must be designed in order for the high performance OTA to be able to drive a small resistance load, such as headphone set. Thus a power amplifier is a good choice to be the output stage. It can be classed in to class A, B, AB, C etc. according to the efficiency of the power delivered to the load. Class AB has a performance that close to class B when the input is high enough to turn the transistors on, and close to class A when the input is small. This feature allows class AB to give a higher power efficiency than class A and less distortion than class B. This project presents a design methodology of a class AB amplifier with a folded cascode amplifier as the first stage, and a push-pull class AB biased output stage. The biasing of folded cascode amplifier was using a wide swing constant transconductance biasing technique, and two floating current sources were used to bias the class AB output to be less sensitive to the supply and process variations. The amplifier has a common-mode input range which is compatible to ground and with rail-to-rail output swing. It provides 56dB open loop gain, and is able to achieve 78 kHz bandwidth at a close loop gain of 40dB. The total harmonic distortion at 40dB close loop gain is 0.1% at maximum output. Corner simulations would be done and changes might be added to allow the designed class AB amplifier works at all corners. To further improve the performance of class AB amplifier, different architectures should be used, such as a three stage amplifier.